2012
DOI: 10.1007/s10517-012-1804-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tenoten on Anxiety and Depression Disorders in Patients with Epilepsy

Abstract: The efficiency and safety of tenoten for anxiety and depression disorders in epileptics has been demonstrated. The drug does not change the incidence and severity of epileptic episodes, does not deteriorate the course of the underlying disease, and can be well combined with anticonvulsants. The results indicate the efficiency of tenoten used to arrest the anxio-depressive disorders in epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The clinical manifestation has certain features of a malfunction in the central nervous system, with repeatability, paroxysms, transience and inflexibility, showing paroxysmal feelings, and automatic nervous dysneuria or a combination of these (1). An epidemiological survey showed that the morbidity of epilepsy in general is 50-70 cases/100,000 individuals (2). Following establishment of treatment, ~80% of epilepsy attacks can be controlled, but ~20% of patients have poor outcomes (3).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical manifestation has certain features of a malfunction in the central nervous system, with repeatability, paroxysms, transience and inflexibility, showing paroxysmal feelings, and automatic nervous dysneuria or a combination of these (1). An epidemiological survey showed that the morbidity of epilepsy in general is 50-70 cases/100,000 individuals (2). Following establishment of treatment, ~80% of epilepsy attacks can be controlled, but ~20% of patients have poor outcomes (3).…”
Section: Introductionmentioning
confidence: 99%
“…RAF of Abs to S100 (the ingredient of Brizantin) previously demonstrated anxiolytic properties confirmed in a number of clinical and preclinical investigations. 21 , 25 29 As antibodies in released-active form are able to modulate the activity of an antigen, the effects mentioned above may be considered in light of numerous functions of S100 protein in the nervous system. 30 33 Also in vivo and in vitro studies have shown interactions of RAF of Abs to S100 with γ-aminobutyric acid (GABA), 34 36 serotoninergic 36 , 37 and dopaminergic system, 36 and glutamate and sigma receptors.…”
Section: Introductionmentioning
confidence: 99%